Study on awareness and perception towards adverse drug reactions among medical and paramedical students in South India - S., Anjali Sruthi; C., Muhas; S., Keerthi; T. R., Anagha; K. M., Abhishek; E. V., Anupama; T., Haritha (International Journal of Research in Medical Sciences, 2022)
Background: Pharmacovigilance (PV) programme targets the monitoring of safety of drugs. It aims at promoting patient care and improving public health and also helps to assess the risk-benefit profile of medicines. The aim of the study was to assess public knowledge about medicine information, safety, and adverse drug reaction reporting (ADR) in medical and paramedical student community. Methods: It was a cross-sectional study conducted among medical and paramedical students for the period of six months from November 2021 to April 2022. The questionnaire was adopted from the literature and was validated. Content and face validities were established, and reliability was assessed. In this study a total of 364 participants returned completed questionnaires. Results: In this study, 364 students completely filled the questionnaire and out of 364 participants, 155 were males (42.58%) and 209 (57.41%) were females. Fourth year students 131 (35.98%) are highly participated in this study and indicated that final year B Pharmacy students having the perceptive knowledge towards ADR. Majority of medical and paramedical students known well about the ADRs. Conclusions: The results of this study highlighted that although the scores for knowledge of medicines, and tendency to report ADR were better, the score for knowledge regarding medication safety was unsatisfactory. There is a need for a regular training and the re-enforcement for the ADR reporting among the health care personnel both medical and paramedical students.